WORD + WORK : Rosemarie Schwarzwälder Galerie nächts St. Stephan. - Schwarzwälder, Rosemarie; Madlener, Elisabeth; Pammiger, Walter (Wien : Galerie nächts St. Stephan Rosemarie Schwarzwälder, 2013)
Kandinsky, Wassily ; Bourgeois, Louise ; Martin, Agnes ; Oppenheim, Meret ; Beuys, Joseph ; Judd, Donald ; Ufan, Lee ; Tuttle, Richard ; Federle, Helmut ; Caramelle, Ernst ; Creischer, Alice ; Gillick, Liam ; Fraser, Andrea ; Fogarasi, Andreas
WORD + WORK, Galerie nächts St. Stephan Rosemarie Schwarzwälder, Wien, 7. September bis 3. Oktober 2013
boek